EFFECT OF VORTEX GENERATORS ON A FRICTION FACTOR IN AN EQUILATERAL TRIANGULAR DUCT - E. A. Zangana, Hamdi (Anbar Journal of Engineering Sciences, 2008)
The main objective of this study is to determine the effect of vortex generators on a friction factor for fully developed flow of a fluid such as air. Longitudinal vortices can be generated in a channel flow by punching or mounting protrusions in the channel wall. Such vortex generators (VGs) can be classified into delta wing, rectangular wing, pair of delta-winglet and pair of rectangular winglet. These longitudinal vortices disrupt the growth of the boundary layer and lead to enhance the heat transfer rate between the working fluid and the conductor channel wall, but this enhancement is associated with increasing in a pressure gradient along the axial length of the channel. So, the friction factor for fully developed air flow in an equilateral triangular duct is investigated experimentally with Reynolds number ranging from (31,000) to (53,000) and the size of the generators was kept constant for three cases which are single, double, and triple pairs of delta–winglet type of vortex generators embedded in the turbulent boundary layer for attack angle of generator of (30, 40, and 50 ) degree. The results show that the friction factor increases by about (43.5 %) when the angle of attack is varied from (30 deg) to (50 deg) for the triple pairs case compared with the base case (without VG).